Investigation of the regularities of physical interactions by means of bonding energy - Мукушев , Б.; Мукушев , Б. А. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The article is devoted to the disclosure of theoretical issues of the phenomenon of binding energy, which occupies a central place in the study of interacting bodies of various nature. The patterns of binding energy are analyzed using the examples of gravitational and electrostatic gravitation of bodies and charges. Using the binding energy equations, the authors have proved the inconsistency of the Thomson model of hydrogen.The article considers the nature of the interatomic interactionby studying the molecular structure of matter. The article calculates the value of the binding energy for these atoms. There are theoreticallyinvestigated regularities of intermolecular interactions occurring in liquids and solids. The stability and instability properties of the atomic nucleus are investigated from the standpoint of the binding energy of the nucleus.